Developing world-class soccer players: An example of the Academy Physical Development Program from an English Premier League team - Ryan, D.; Lewin, C.; Forsythe, S.; McCall, A. (Strength and Conditioning Journal, 2018)
The role of the youth academy in elite soccer is to create world-class players. This involves targeted development of a myriad of factors, including technical, tactical, psychological, and physical qualities. The role of sports science and medicine is to optimize the physical development of young promising players. In line with the multifaceted nature of player development, the sports science and medicine department must integrate effectively into the overall youth academy. The purpose of the present article is to outline the objectives, methods, and operations of a sports science and medicine department of one of the biggest soccer teams in the world.